Inhibitor of apoptosis-stimulating p53 protein protects against inflammatory bowel disease in mice models by inhibiting the nuclear factor kappa B signaling. (7th June 2021) - Qian, Ke; Yuan, Lianwen; Wang, Shalong; Kuang, Yong; Jin, Qianqian; Long, Dongju; Jiang, Yuhong; Zhao, Hua; Liu, Kuijie; Yao, Hongliang
Summary: Drugs and therapies available for the treatment of inflammatory bowel disease (IBD) are not satisfactory. Our previous study has established the inhibitor of apoptosis-stimulating p53 protein (iASPP) as an oncogenic regulator in colorectal cancer by forming a regulatory axis or feedback loop with miR-124, p53, or p63. As iASPP could target and inhibit nuclear factor kappa B (NF-κB) activation, in this study the role and mechanism of iASPP in IBD was investigated. The aberrant up-regulation of iASPP in IBD was subsequently confirmed, based on online data sets, clinical sample examinations and 2, 4, 6-trinitrobenzene sulfonic acid (TNBS)- and dextran sulfate sodium (DSS)-induced colitis mice models. TNBS or DSS stimulation successfully induced colon shortness, body weight loss, mice colon oxidative stress and inflammation. In both types of colitis mice models, iASPP over-expression improved, whereas iASPP knockdown aggravated TNBS or DSS stimulation-caused colon shortness, body weight loss and mice colon oxidative stress and inflammation. Meanwhile, in both types of colitis mice models, iASPP over-expression inhibited p65 phosphorylation and decreased the levels of tumor necrosis factor (TNF)-α, interleukin (IL)-1β, IL-6, C-X-C motif chemokine ligand (CXCL)1 and CXCL2 in mice colons, whereas iASPP knockdown exerted opposite effects. Graphical Abstract: